2016
DOI: 10.5455/ijmsph.2016.0108201540
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge regarding noncommunicable diseases and their risk factors among students of higher secondary school: an interventional study

Abstract: Chronic diseases are defined as "an impairment of bodily structure and/or function that necessitates a modification of the patient's normal life, and has persisted over an extended period of time." Globally, noncommunicable Diseases (NCDs) are increasingly recognized as a major cause of morbidity and mortality. The World Health Report 2001 had indicated that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 3 publications
3
15
1
Order By: Relevance
“…However, Shivalliet al reported 30.5% and 27.3% rates of awareness among intermediate school students from Varanasi which is comparable to our study findings [15]. Similar findings were reported in study by Chaudhari et al which concluded that baseline knowledge of students regarding risk factors of hypertension was unsatisfactory [16]. Similarly, knowledge about risk factors of hypertension was present in only a third of the Thai students and lifestylerelated risk factors which were common to all cardiovascular diseases were not well known in the study by Lorgaet al [17].…”
Section: Fig-1: Mean Scores Of Pre Test and Post Testsupporting
confidence: 90%
See 1 more Smart Citation
“…However, Shivalliet al reported 30.5% and 27.3% rates of awareness among intermediate school students from Varanasi which is comparable to our study findings [15]. Similar findings were reported in study by Chaudhari et al which concluded that baseline knowledge of students regarding risk factors of hypertension was unsatisfactory [16]. Similarly, knowledge about risk factors of hypertension was present in only a third of the Thai students and lifestylerelated risk factors which were common to all cardiovascular diseases were not well known in the study by Lorgaet al [17].…”
Section: Fig-1: Mean Scores Of Pre Test and Post Testsupporting
confidence: 90%
“…Before and after the sessions the knowledge of students was tested by administering the pre-designed, pre-tested proforma. The proforma consisted of16 questions with 4 questions on each of the non communicable diseases. The impact was evaluated by comparing the scores in pre and post test proformas.…”
mentioning
confidence: 99%
“…The awareness level of the study participants regarding NCDs and their risk factors was unsatisfactory. 11 Many studies have been conducted on students for awareness of NCDs from different parts of India and abroad. While comparability of these studies could obviously be limited (awareness has multiple determinants), some may be quoted for their scope.…”
Section: Discussionmentioning
confidence: 99%
“…The awareness level of the study participants regarding NCDs and their risk factors was unsatisfactory. 12 Many studies have been conducted on students for awareness of NCDs from different parts of India and abroad. While comparability of these studies could obviously be limited (awareness has multiple determinants), some may be quoted for their scope.…”
Section: Resultsmentioning
confidence: 99%